Gênero relato de experiência: um olhar sobre as estratégias cognitivas e discursivas em aquisição de linguagem - Carvalho, Maria José Lima de (2011)
This research paper has the aim to contribute to the insertion of oral practices in the classroom under an interactive approach. Starting from this language notion, we intend to investigate the child speech in order to better understand the acquisition process by means of little explored genres in the context of linguistic research. We have turned to the genre category as a communication model (Marcuschi, 2008), because we understand that language stands out through use, by means of effective interactive situations experienced by subjects (Bakhtin, 2000). We have investigated children s verbal actions in the case report genre, occurring in spontaneous situations and based on the assumption that word expression is only possible through speaker s co-participation. This means that the child penetrates the language by another s partnership in the interaction (PERRONI,1992) and, through such an action, he/she learns values in addition to reproduce cultural behaviors. According to this focus, language claims the development of a communicative competence on the part of subjects, mostly because it is part of a social demand even more essential in the construction of modern societies. With this purpose, we refer to Bakhtin s (2000), Marcuschi s (2008), and Schneuwly s (2010) theoretical principles, who discuss the understanding of language interconnected to the broadest social-historical contexts, as well as a more specific theory about the case report genre. We also make a link to authors who deal with language acquisition (Perroni, 1992), in order to analyze and describe child s speech with a special view to gestural and verbal movements made by children when they construct the genre in diversified uttering contexts. We have studied the data through a qualitative approach and proven the supposedly raised hypothesis: when children interact, they use different cognitive, discursive strategies to meet their needs of communication , an ability that involves communicative construction supported by different genres dug in natural aspects of similarities which are characteristic among them. By the exposed, we confirm the proposal: Referential for Child Teaching (1998), to recognize oral genres as legitimate instruments of teaching and knowledge acquisition, because, besides being a practice that precedes writing, it is one of the most essential and recurring communication activities for the social practices functioning.